The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11064-011-0595-y
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Postischemic Hypoperfusion by Tempol: Endothelial Signal Transduction Mechanism

Abstract: This report entails in vivo and in vitro studies concerned with free radical species involved in brain ischemia. The participation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in the early manifestation of cerebral ischemia/reperfusion was investigated in gerbils exposed to transient global ischemia using 4-OH-2,2,6,6-tetramethylpiperidine-1-oxyl (TPL), a well-known antioxidant. TPL treatment reversed cerebral postischemic hypoperfusion and tissue edema in these animals. The findings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…66 Okada reported in transient global ischemia that CBF changes at the induction of ischemia and also at reperfusion within 1 min. 67 Westermaier et al saw local cortical blood flow drop in 1 min while pO 2 dropped in 2−3 min in a subarachnoid hemorrhage model. 68 Prunell determined, also in a subarachnoid hemorrhage model, that CBF dropped in 40 s while pO 2 reached a minimum in 1.5−2 min.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…66 Okada reported in transient global ischemia that CBF changes at the induction of ischemia and also at reperfusion within 1 min. 67 Westermaier et al saw local cortical blood flow drop in 1 min while pO 2 dropped in 2−3 min in a subarachnoid hemorrhage model. 68 Prunell determined, also in a subarachnoid hemorrhage model, that CBF dropped in 40 s while pO 2 reached a minimum in 1.5−2 min.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…More quantitatively, Peters et al found changes in cortical CBF within 5 min (the shortest time measured) after induction of focal ischemia and again at reperfusion . Okada reported in transient global ischemia that CBF changes at the induction of ischemia and also at reperfusion within 1 min . Westermaier et al saw local cortical blood flow drop in 1 min while pO 2 dropped in 2–3 min in a subarachnoid hemorrhage model .…”
Section: Resultsmentioning
confidence: 98%
“…Stabilization of calcium homeostasis may be in part supported by treatment with lithium, 46 magnesium, 47 and calcium channel blockers such as nimodipine. 48,49 Although these agents may or may not be effective when given alone, they may be combined with free radical scavengers 50,51 such as resveratrol, 52,53 tempol, 54 and edaravone. 55 Another approach is to combine agents that inhibit mitochondrial damage with those that support mitochondrial function.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…Inducible nitric oxide synthase (iNOS), a subtype of nitric oxide synthase that is only induced under pathological conditions, is regulated by NF-κB. When iNOS is activated, it can release a large amount of NO, which leads to the excessive production of ROS/RNS [33][34][35][36]. In the brain, the unchecked ROS/RNS release leads to lipid peroxidation of cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, the unchecked ROS/RNS release leads to lipid peroxidation of cell membranes. This in turn disrupts phospholipid-dependent enzymes and ionic gradients resulting in other sequelae, including disturbances of the CBF, BBB permeability changes, and the development of edema [33]. Among the many studies concerning the role(s) of ROS/RNS molecules are those that have demonstrated their major role in the signal transduction pathways associated with vascular contraction and relaxation [33,37].…”
Section: Introductionmentioning
confidence: 99%